Pencemaran Logam Berat Cd, Ni Dan Fe Pada Endapan Sedimen Sungai Daerah Tinanggea Konawe Selatan Sulawesi Tenggara - Wahyu Ekawati; Muhammad Chaerul (Jurnal Lingkungan Almuslim, 2022)
The purpose of this research is to analyze the level of heavy metal contamination and get pollution status on KEM river sediment in Tinanggea village, Konawe district south, Southeas Sulawesi Province covering cadmium(Cd), Nickel(Ni), Iron(Fe).The method of sampling using grab sampling method and hevy metal analysis method was done Laboratory using Atomic Absorbtion Spectrophotometry(AAS), the continued with data analysis using United states Enviromental Protection Agency (US EPA) standard quality standard. The test results of heavy metal samples which include Cadmium (Cd), Iron(Fe), Nickel(Ni) on KEM river deposits in Tinanggea area.Where at the six sampling stations have indicated an indication of contamination Nickel, that is at first station with value 24,21 mg/kg, at station four namely 27,51 mg/kg, quality standard for nickel 21 mg/kg. Parametes have exceeded the sediment quality standard.This shows that the KEM river in the Tinanggea area has been polluted by nickel heavy metal elements, but it is still classified as mildly polluted.